Anthropometry and Metabolic Abnormalities in Obese Children with Non Alcoholic Fatty Liver Disease - Shelim, Rumana; Ikram, Shuma; Ratan, Naim Hossain; Hossain, Mohammod Moqbul; Mohsin, Fauzia (East West Medical College Journal, 2025)
Background: Obesity has emerged as a global epidemic in children with a spectrum of psycho-social and medical consequences manifesting across the lifespan. Obesity-related morbidities that emerge early in childhood are an alteration in glucose metabolism and fatty infiltration of the liver. Non-alcoholic fatty liver disease (NAFLD), chronic liver disease is a metabolic complication of obesity. Objective: To identify the prevalence of NAFLD among obese children and anthropometric and metabolic abnormalities among these obese children with NAFLD. Methodology: This was a cross sectional study included 50 obese children and adolescents, attending Paediatric Endocrine OPD, BIRDEM from June 2010 to December 2010. BMI e” 95th centile for age and sex was used as an anthropometric marker to diagnose obesity. Obesity with dismorphism, endocrine, chromosomal abnormalities, chronic liver diseases due to infectious or metabolic causes were excluded from the study. Fasting blood samples were collected for measurement of blood glucose, lipid profile, FT4, TSH and SGPT. Fatty liver was diagnosed by USG which includes increased echogenicity of liver, blurring of vascular margins and increased acoustic attenuation. Results: The prevalence of fatty liver disease among obese children was 36% with male predominance(M72.2%, F 27.8%). Mild NAFLD was 72% followed by moderate 28%. High Cholesterol, high LDL and high SGPT were more prevalent in obese children with NAFLD which was statistically significant (P <0.004, <0.05and <0.04 respectively. Conclusion: Obesity with liver disease can get overlooked among the plethora of adverse outcomes related to childhood obesity. Our study was attempted to find out the obese children with NAFLD and related metabolic abnormalities, so that delebarate strategies could be taken to prevent this irreversible liver damage among obese children. EWMCJ Vol. 13, No. 1, January 2025: 17-22